Identifying Victims of Human Trafficking in Central Pennsylvania: A Survey of Health-Care Professionals and Students. Issue 2 (3rd April 2019) - Sinha, Risha; Tashakor, Elahe; Pinto, Casey
ABSTRACT: Objective : To assess Central Pennsylvania health-care professional and student knowledge, beliefs, and awareness of human trafficking. Methods : An anonymous online public survey URL was distributed from May through July 2017 at two academic health-care systems and one medical school in Central Pennsylvania to 4, 925 health-care professionals and students. Results : The majority of participants exhibited at least moderate knowledge of human trafficking (96.88%) but indicated they did not feel confident identifying victims (47.51%). Despite lacking confidence, 57.06% agreed they would likely encounter victims in their current or future practice. Participants with previous training had a higher human-trafficking knowledge score than those without. Conclusions : Within this study, participants with training to identify victims of human trafficking demonstrated a greater degree of knowledge, comfort, and confidence with respect to identifying victims of human trafficking in comparison to their untrained counterparts. This research further supports the need for policies requiring health-care providers and other first responders to have training to identify and intervene on behalf of victims of human trafficking.